Logo Analysis Of Meta Bright Vision Company Using The Semiotic Theory - Auliazmi, Rizki (Universitas Ciputra, 2019)
A logo will make an indirect communication through visual form and give a message to the target, the logo acts as the sender of the message in a visual form that has meaning. A training and consulting company named Meta Bright Vision has a logo that is needed to give perception to the public and business partners about the vision and mission of the company, by using a visual logo that has a meaning called a logo. The analysis uses a semiotic theory approach from Peirce, John Fiske, and Saussure. And discuss in terms of aesthetics in the visual work of the logo. The semiotics approach is used to find the meaning contained in the visual logo and determine how the logo has been able to send messages to the recipient of the message.